The non-compact left ventricle cardiomyopathy: clinical features and diagnostic capabilities - E. A. Mershina; R. P. Myasnikov; O. V. Kulikova; M. S. Kharlap; S. N. Koretskiy; O. M. Larina; V. E. Sinitsyn; S. A. Boytsov (Столичная издательская компания, 2015)
The non-compact left ventricular cardiomyopathy (NCLVC) refers to the non-classified cardiomyopathies. Its cause is not completely clear. NCLVC is characterized by an increased trabecular with the formation of deep intertrabecular crypts. It can exist either in isolated form or in combination with other congenital diseases. The clinical features of NCLVC are different: asymptomatic forms are identified as well as forms with the progressive course of the disease, with heart failure, angina, thromboembolic complications, and ventricular arrhythmias. In some cases, the disease starts with the sudden cardiac death. The sudden decompensation of NCLVC also could arise due to the development of acute myocarditis